Analisis Penambatan dan Simulasi Dinamika Molekular Komplex Siklookgesinenase-2 dengan Beberapa Senyawa Turunan Kuinazolinon - Yanuar, Arry; Setiajid, Muhammad Aditya; Hayun, . (Jurnal Farmasi Indonesia, 2014)
The aims of this research is to observe the inhibition activity of sulfonamides or sulfacetamides substituted of 3-Phenyl-2-styril-4(3H)-quinazolinones with COX-2. The study of COX-2, binding inhibition and dynamics interaction was done with in silico method by molecular docking with Auto Dock 4.0 and molecular dynamics in 2 nanoseconds with Amber 11. Those compound could be divided into 3 groups, based on Î?G scores of docking result: very selective group (-10.92 to -11.33 kcal/mol) compared to SC-558 (-10.90 kcal/mol); selective group compound (-9.22 to -10.68 kcal/mol) compared to celecoxib (-10.63 kcal/mol); non selective group, compound (-6.48 to -6.98 kcal/mol) compared to aspirin (-4.82 kcal/mol). Molecular dynamics simulation of 6COX complex with several quinazolinon derivates showed number and stability of hydrogen bond.Keywords : COX-2, anti-inflammatory, molecular docking, molecular dynamics.